If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+9-6(x+1)=4+5
We move all terms to the left:
3x+9-6(x+1)-(4+5)=0
We add all the numbers together, and all the variables
3x-6(x+1)+9-9=0
We add all the numbers together, and all the variables
3x-6(x+1)=0
We multiply parentheses
3x-6x-6=0
We add all the numbers together, and all the variables
-3x-6=0
We move all terms containing x to the left, all other terms to the right
-3x=6
x=6/-3
x=-2
| 4x+(3x+5)=145 | | -12p+3=-14p+9 | | -5(2x=3) | | 0.06(x+20)+0.08(x−10)=4.6 | | 8f=7f+15 | | 100x+160=300 | | 2/3s=2 | | 15x+90+x=180 | | -6-15d=9+9-12d | | -(x-8)+4x=2(x+4)=x | | x+6+5x=90 | | 9-13q=-4q | | 8x+2(1.5x)=350 | | (4x+6)=(1.5x+41) | | p-5-6p-8=-1-p | | 6(4+v)+35v=11v | | 7.32x=-13.2 | | 40n=5 | | q=1+3/4q | | 7.32x=13.2 | | -7.02+2.9u+16.1u=6.93+19.9u | | 8x-(3x-15)=60 | | .20(n-3)=2n | | X-14=-8x+13 | | 8-8v=-3(8+2v)-6v | | 5x+200=-450 | | (4x+6)=(3/2+41) | | 8x+13=x-14 | | 6(−2g−1)=−(13g+2)g= | | 1/5(n-3)=2(n) | | 3(x-1)-2x=-2X=3x(4x=2) | | 3x+12.6=122.4 |